Pathological and clinical impact of neoadjuvant chemoradiotherapy using full‐dose gemcitabine and concurrent radiation for resectable pancreatic cancer. Issue 2 (February 2013) - Sho, Masayuki; Akahori, Takahiro; Tanaka, Toshihiro; Kinoshita, Shoichi; Tamamoto, Tetsuro; Nomi, Takeo; Yamato, Ichiro; Hokuto, Daisuke; Yasuda, Satoshi; Kawaguchi, Chihiro; Nishiofuku, Hideyuki; Marugami, Nagaaki; et al.
Abstract Background/purpose The therapeutic options available as preoperative strategies for resectable pancreatic cancer have received worldwide attention. We have recently introduced neoadjuvant chemoradiotherapy (NACRT) to achieve local control and possibly complete cure. In this study, we have retrospectively evaluated its impact on pathology and the perioperative clinical course in addition to its safety. Methods Sixty‐one patients who received full‐dose gemcitabine (1000 mg/m2) preoperatively with concurrent radiation (50 or 54 Gy) were evaluated. Seventy‐one patients who received no preoperative therapy served as controls. Perioperative outcomes, postoperative complications, immunonutritional status, and the performance of adjuvant chemotherapy were compared. Results Fifty‐nine patients (97 %) completed NACRT. Toxicity was acceptable and the regimen was feasible as outpatient treatment. The perioperative outcomes were closely comparable to control. The rate of pancreatic fistula was lower and hospital stay was shorter in the NACRT group. The rate of lymph node metastasis and stage was lower in the NACRT group. Furthermore, R0 resection could be achieved in 92 % of patients treated with NACRT. Nutritional status decreased after NACRT and further deteriorated during adjuvant chemotherapy. The initiation of postoperative chemotherapy was delayed in the NACRT group. Conclusions Our current protocol of neoadjuvant chemoradiotherapy is feasible and substantially improves the pathology. However, it has some detrimental effects on postoperative nutritional status and performance of adjuvant chemotherapy. Furthermore, it should be noted that there is a possibility of arterial complications.